Legal pathology of property acquisition in dilapidated context with historical value by the municipality (case study: Sari city) - alijan shamshirband; Reza Nasiri Larimi; Seyed Mehdi Ahmadi (تحقیقات کاربردی علوم جغرافیایی)
One area of activity that receives considerable attention in municipalities, particularly in metropolitan regions, is the management of properties assigned to municipalities for the implementation of detailed plans, comprehensive urban development strategies, and revitalization and renovation initiatives for deteriorated areas. Annually, municipalities engage in the construction or enhancement of road infrastructure and the establishment of recreational and cultural facilities in alignment with urban development and city expansion objectives. The objective of this research is to elucidate the legal issues associated with property ownership in deteriorated areas of historical significance as managed by the municipality of Sari. This study adopts a descriptive-analytical framework, employing an applied-developmental research approach grounded in survey and field methodologies. The data collection strategy utilized in this research comprises library research, document analysis, and field surveys, employing questionnaires administered to a sample of 384 citizens of Sari. Data analysis in this study employs chi-square statistical techniques using SPSS software. The findings reveal that the primary organizational challenges encountered by the municipality in terms of property ownership in deteriorated areas of Sari include insufficient awareness of laws and legal procedures, lack of coordination in implementation processes, failure to regularly update property pricing tariffs, delayed and unplanned project execution, and the absence of legal analyses in project preparation. Consequently, the municipality of Sari should prioritize the enhancement of its internal structure and operational performance, addressing identified weaknesses and fostering structural and functional coherence in property ownership as part of revitalization plans for deteriorated areas, rather than concentrating exclusively on external and inter-organizational dimensions.